Una nueva especie de serpiente del género Sibon (Serpentes: Colubridae) de la vertiente del Caribe de Costa Rica - Alejandro Solórzano (Revista de Biología Tropical, 2001)
Sibon lamari, a new species of colubrid snake from northeastern Costa Rica is described on the basis of six specimens. The new form differs from the closely allied S. annulatus in color pattern, head size, subcaudal count, and number of labials bordering eye-orbit. This is the third species of Sibon, together with S. argus and S. longifrenis, possessing a green dorsal ground color in Costa Rica. Sibon lamari coexists sympatrically with S. annulatus, S. argus, S. longifrenis and S. nebulatus at the locality of Guayacán de Siquirres (Limón Province)